Hydro-morphological stressors reduce distribution range and affect population status of cyprinid fishes in Austria - Hayes, Daniel S.; Schaufler, Gregor; Schmutz, Stefan; Unfer, Günther; Führer, Simon; Auer, Stefan; Seliger, Carina (Frontiers in Environmental Science, 2022)
Rivers worldwide have been transformed into fragmented, impounded, channelized, and flow-regulated ecosystems. These anthropogenic transformations can reduce fish distribution and population status, especially of those species belonging to medium- or long-distance migratory guilds and those dependent on free-flowing rivers and intact sediment and habitat conditions. Here, we aim to understand how different hydro-morphological pressure types affect the distribution and population status of key potamodromous fish species of the rheophilic and lithophilic fish guild, the barbel (Barbus barbus) and the nase (Chondrostoma nasus). We also assess the status of chub (Squalius cephalus) to include a species less sensitive to habitat degradation. For the first time, we assembled an extensive Austrian-wide GIS-based fish sampling database with hundreds of biological surveys, allowing us to analyze quantitatively >4,000 river kilometers for presence/absence and population status of target fishes and to assess population status where the species is present. The data reveal that the distribution range of target species decreased by around 40–60% compared to their natural ranges according to the reference standard (Leitbild). Hydro-morphological pressures affect target species’ population biomass, and trends between impact types can be detected. Chub and barbel exhibit the highest median biomass in free-flowing rivers and residual flow reaches, followed by reservoir sections. Of all pressure types, population biomass is lowest in hydropeaked river stretches. Nase biomass has a grand median of 0.0 kg/ha across all sites, showing hardly any differences between hydro-morphological pressure types. Overall, our results show a drastic shrinkage of the distribution range of three cyprinid fish species previously prominent in Austria. By linking current population vitality to hydro-morphological stressors and ecological status assessments, this study sets a baseline for data-based conservation actions of (Red-listed) species as well as policy and management frameworks.